2019
DOI: 10.3889/oamjms.2019.437
|View full text |Cite
|
Sign up to set email alerts
|

Viral and Host Factors are Related to the Progression of HIV Diseases in Mimika, Papua

Abstract: BACKGROUND: Papua has a high cumulative number of HIV, which has expanded epidemic status with the most risk factors are heterosexuals. AIM: This study aims to determine factors associated with HIV disease progression include host and viral factors. METHODS: Eighty-four subjects recruited in Rumah Sakit Mitra Masyarakat (RSMM) VCT’s laboratory, interviewed with questionnaires and also did laboratory examinations. HIV-1 subtypes were identified using RT-PCR, nested PCR and sequencing. Then, CD4+ dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This concern is illustrated by HIV-2 and group O strains of HIV-1, which possess intrinsic resistance to NNRTIs [ 25 27 ]. Among others, it was also proven that likelihood of AIDS developing was increased in the patients infected with a non-A subtype, in others studies such connection was not confirmed [ 28 32 ]. In our trail 26% of Ukrainian (79% of all cohort infected with subtype A) versus 50% of Polish patients (75% of all cohort with subtype B) were late presenters (p < 0.05), which is consistent with the results from previously performed studies [ 28 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concern is illustrated by HIV-2 and group O strains of HIV-1, which possess intrinsic resistance to NNRTIs [ 25 27 ]. Among others, it was also proven that likelihood of AIDS developing was increased in the patients infected with a non-A subtype, in others studies such connection was not confirmed [ 28 32 ]. In our trail 26% of Ukrainian (79% of all cohort infected with subtype A) versus 50% of Polish patients (75% of all cohort with subtype B) were late presenters (p < 0.05), which is consistent with the results from previously performed studies [ 28 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among others, it was also proven that likelihood of AIDS developing was increased in the patients infected with a non-A subtype, in others studies such connection was not confirmed [ 28 32 ]. In our trail 26% of Ukrainian (79% of all cohort infected with subtype A) versus 50% of Polish patients (75% of all cohort with subtype B) were late presenters (p < 0.05), which is consistent with the results from previously performed studies [ 28 , 31 , 32 ]. Such high prevalence of AIDS-defining diseases in our cohort (38% of all recruited patients) can be also the result of the characteristic of the sites of the recruitment: most of the centers were clinical departments, mostly the diagnosis were made because of the severe state of the patients—they sought medical care (hospitalization) due to poor general state and not due to a risky behavior in the individual anamnesis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, weather conditions significantly influence disease development, where moisture levels can impact the survival of propagules, thereby affecting both the initiation and severity of epidemics [ 9 ]. In the context of HIV infection, a multitude of factors, including immunological, virological, environmental, and genetic variables, contribute to disease progression [ 10 ]. In the case of PTA, the trauma inflicted on the joint can result in damage to the articular cartilage, weakening its integrity and paving the way for the development of PTA.…”
Section: Reviewmentioning
confidence: 99%
“…Two factors that influence the progression of HIV disease were HIV subtypes (p = 0.002) and Body Mass Index (p = 0.033). The HIV-1 subtype also correlated with CD4+ levels with a value of p = 0.04 (Widiyanti & Hadi, 2019). 12 Ending the epidemic of HIV/AIDS by 2030: Will there be an endgame to HIV, or an endemic HIV requiring an integrated health system response in many countries?…”
Section: Quantitativ E Indonesiamentioning
confidence: 99%